Human Capital Education Management and Supply Chain Recovery Strategies in State-Owned Construction Companies: PT Waskita Karya Economic Equilibrium Approach - Buyung W Prinatama (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2026)
PT Waskita Karya (Persero) Tbk (WSKT) faces significant challenges in procurement management, leading to project delays and cost overruns. This study aims to analyze the causes of low vendor participation through the perspective of supply-demand curves and proposes strategic solutions to restore market equilibrium. The methodology employed is a case study with a qualitative descriptive analysis, supported by microeconomic modeling. The results indicate that supply inelasticity, driven by payment risks, causes a leftward shift in the supply curve, creating a deadweight loss. This article recommends five integrative strategies: the establishment of a Vendor Support Center (WISE), Debt-to-Asset Shareholding negotiations, dynamic pricing mechanisms, the use of Memorandums of Understanding (MoU) during the tender phase, and early completion incentives. Moving beyond traditional operational perspectives, the study offers original contributions through the quantification of deadweight loss caused by vendor payment risks and the introduction of the WISE framework to restore supply elasticity. Key innovations include a unique "Debt-to-Asset Shareholding" model that converts liabilities into strategic asset equity, and the adaptation of dynamic pricing to mitigate international material price volatility. By utilizing a sequential supply curve recovery model, this research provides a new methodology for synchronizing legal commitments and performance-based incentives to achieve high-output market equilibrium.